Poverty and the Production of World Politics - Ryner, Magnus. author. aut Link
XIV, 306 p.
Keywords: This book revisits Cox and Harrod's conception of 'unprotected workers' through theoretical reflection and empirical explorations of the rise of millennialism, prostitution and the sex industry, the politics of migration, the interstices of class and gender, and trade union politics.